2021
DOI: 10.1021/acsanm.1c00143
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Carbon-Wrapped Cobalt–Manganese Oxide Nanosheets Loaded into a Three-Dimensional Graphene Nanonetwork as a Free-Standing Anode for Lithium-Ion Storage

Abstract: A high-quality and centimeter-level three-dimensional (3D) nitrogen-doped graphene (NG) nanonetwork is synthesized via a chemical vapor deposition method to serve as a substrate and a current collector, which directly germinates active metal oxides to act as a free-standing electrode in lithium-ion batteries. By means of facile electrodeposition and annealing processes, the tetragonal spinel cobalt–manganese oxide nanosheets wrapped with polypyrrole pyrolytic carbon are in situ hybridized with a 3D NG nanonetw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This approach ensures uniform sodium stripping/deposition, mitigates Na dendritic formation, lowers local current density, and minimizes electrode size variations. 18,19 For example, the Sun and his coworkers have carbonized cotton cloth to form a 3D carbon material with sodiophilicity, and injected molten sodium into the above framework to synthesize the composite anodes, which showed excellent stability and cycling performance. 20 Besides, Dong et al, employed the copper phosphide mesh as the current collector for sodium metal electrodeposition, enhancing the battery performances dur to their good sodiophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…This approach ensures uniform sodium stripping/deposition, mitigates Na dendritic formation, lowers local current density, and minimizes electrode size variations. 18,19 For example, the Sun and his coworkers have carbonized cotton cloth to form a 3D carbon material with sodiophilicity, and injected molten sodium into the above framework to synthesize the composite anodes, which showed excellent stability and cycling performance. 20 Besides, Dong et al, employed the copper phosphide mesh as the current collector for sodium metal electrodeposition, enhancing the battery performances dur to their good sodiophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, TMS growth on free-standing collectors as working electrodes, such as carbon paper, carbon cloth, and metal foam, has become a new exploration target. 20,21 High mechanical strength self-supported electrodes are advantageous for full active site exposure and improved electrical conductivity. 22,23 Lately, three-dimensional nitrogen-doped porous graphene (NPG) foam has been shown to be utilized as a self-supported substrate without a binder to increase the reversible capacity by increasing the active surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown the possibility to completely eliminate CCs by fabricating free-standing electrodes (FSEs). ,, Many metal-foil-free CCs have previously been produced using a variety of active materials and manufacturing methods, including slurry-casting on glass, high-pressure/high-temperature filtration, , and 3D printing. , Unfortunately, most of these FSEs suffer from low specific capacities due to poor accessibility of active materials or insufficient electronic conductivities through the scaffolding matrix. Cathode active materials are currently the most expensive components of LIB electrodes and therefore must be fully utilized to obtain commercial viability.…”
Section: Introductionmentioning
confidence: 99%